The Role of Social Media Activities to Enhance Brand Equity - Angga Febrian; Dhiona Ayu Nani; Lia Febria Lina; Nurul Husna (Universitas Hayam Wuruk Perbanas, 2022)
The direct impact of the economic downturn due to Covid-19 is mainly perceived by Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine how MSMEs can understand customer needs regarding the provision of social media quality that can improve brand image and brand awareness. The survey was conducted on 145 respondents who had online shopping experience using social media by utilizing the structural equation modeling approach. Results show that social media quality can increase brand awareness, brand image, and social media marketing activities. Therefore, marketers who use social media can focus on its constituent indicators including content quality, design quality, information quality, interaction quality, contact availability, and contact relevance. Customers will have a high level of brand awareness and a good brand image if marketers can provide social media quality to meet customer demands. While previous studies found that there is a positive relationship between social media marketing activities on brand image and brand awareness, this study shows the opposite result because customers are not affected by the activities carried out by social media. This is considered a usual activity that other marketers also carry out. The implication of this study is that good social media quality is needed to increase brand awareness, brand image, and social media marketing activities.